Pelatihan Calon Asisten Ombudsman Republik Indonesia: Mewujudkan Profesionalisme dan Representasi Sosial dalam Lembaga Pengawas Pelayanan Publik - Rangga Aditya Pranata; Muhammad Khoirul Anwar; Dawam Muzakki (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to examine the urgency of training prospective Ombudsman Assistants of the Republic of Indonesia in shaping professionalism and strengthening social representation within the public service supervisory institution. Ombudsman Assistants play a strategic role as technical supervisors who interact directly with public reports, thus requiring high competence and a strong professional attitude. This study uses a qualitative-descriptive approach with a literature study method. Data were collected from various legal sources and scientific literature, including laws and regulations, Ombudsman RI policy documents, and relevant articles and opinions. The analysis was carried out thematically to see the relationship between training policies, career systems, and socio-cultural aspects. The results of the discussion show that training not only equips prospective assistants with technical competence and professional ethics, but also plays a role in shaping an inclusive and adaptive institutional identity to the diversity of society. The synergy between training and the career development system is the key to the success of the Ombudsman RI in producing professional, integrated, and representative human resources.